Hungarian Monitoring, 3 March 1988 . [Magyar rádiófigyelő], 1988. március 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - US must guarantee working of PLO office - NATO summit conference - Disturbances in the Caucasus region - Encouraging signs for a Nicaraguan agreement Domestic Affairs: - Károly Grósz receives the NATO parliamentary delegation - Gabčíkovo-Nagymaros dam: Hungarian slippage - West German-Hungarian relations - Sitting of the Budapest Crime Prevention Council - Situation of the unemployed - Question of handling dangerous waste Economy: - Director of the Industrial Institute on the national income Külpolitika: - Az Egyesült Államok köteles a PFSZ-iroda működését biztosítani - NATO csúcsértekezlet - Kaukázusi zavargások - Kedvező jelek a nicaraguai megegyezésre Belpolitika - Grósz Károly fogadta a parlamenti NATO küldöttséget - Bős-nagymarosi vízlépcső: magyar csúszás - NSZK - Magyar kapcsolatok - A Fővárosi Bűnmegelőzési Tanács ülése - Munkanélküliek helyzete - Veszélyes - Hulladék kezelés kérdése Gazdaság: - Az ipargazdasági intézet igazgatója a nemzeti jövedelemről